What the Heart Brings to Therapy: A Systematic Review on Heart Rate Variability Contributions to Psychotherapy Research; [Lo Que el Corazón Trae a la Terapia: Una Revisión Sistemática de Las Contribuciones de la Variabilidad de la Frecuencia Cardíaca a la Investigación en Psicoterapia] - Fernandez-Tapia, A (Asoc. Espanola de Psicologia Clinica y Psicopatologia, 2023)
Vagal tone is a psychophysiological construct indexed by heart rate variability (HRV) that is associated with emotion regulation, interpersonal abilities, and mental health in nonclinical and clinical populations. However, the evidence concerning its role in psychotherapy is still limited and no review summarizing the obtained results has been reported to date. The present study aims to fill this gap by presenting a systematic review of psychotherapy studies that evaluate patients’ vagal tone regarding process variables and therapy outcomes. The databases SSCI (WoS), EBSCO, and Psychology (ProQuest) database were searched, yielding a total of 23 studies that were qualitatively analyzed. Results showed mixed evidence regarding the predictive value of HRV for clinical outcomes (e.g., symptom level), as well as the effects of psychotherapy on HRV. The association between HRV and working alliance has shown to be consistently positive, although in a smaller number of investigations. Findings are discussed considering HRV assessment conditions and study designs, highlighting the potential value of HRV to inform about the level of psychophysiological resources and autonomic flexibility that individuals bring to therapy. © 2023 Asoc. Espanola de Psicologia Clinica y Psicopatologia. All rights reserved.